Description of two new species of Stenocatantops (Orthoptera: Acrididae: Catantopinae) from Taiwan with a key to known species of genus - Yin, Hong; Yin, X.-C. (Zootaxa, 2005)
Two new species [i.e. Stenocatantops nigrovittatus, sp. nov. and Stenocatantops unicolor, sp. nov. ] of the genus Stenocatantops Dirsh (Orthoptera, Acrididae, Catantopinae) from Taiwan, China are described in this paper. A key to known species of the genus is given. The type specimens are deposited in the Department of Entomology, National Taiwan University (NTU), Taiwan.